Neuroprotective response after photodynamic therapy: Role of vascular endothelial growth factor - Suzuki, Misa (BioMed Central, 2011)
BACKGROUND: Anti-vascular endothelial growth factor (VEGF) drugs and/or photodynamic therapy (PDT) constitute current treatments targeting pathological vascular tissues in tumors and age-related macular degeneration. Concern that PDT might induce VEGF and exacerbate the disease has led us to current practice of using anti-VEGF drugs with PDT simultaneously. However, the underlying molecular mechanisms of these therapies are not well understood. METHODS: We assessed VEGF levels after PDT of normal mouse retinal tissue, using a laser duration that did not cause obvious tissue damage. To determine the role of PDT-induced VEGF and its downstream signaling, we intravitreally injected a VEGF inhibitor, VEGFR1 Fc, or a PI3K/Akt inhibitor, LY294002, immediately after PDT. Then, histological and biochemical changes of the retinal tissue were analyzed by immunohistochemistry and immunoblot analyses, respectively. RESULTS: At both the mRNA and protein levels, VEGF was upregulated immediately and transiently after PDT. VEGF suppression after PDT resulted in apoptotic destruction of the photoreceptor cell layer in only the irradiated area during PDT. Under these conditions, activation of the anti-apoptotic molecule Akt was suppressed in the irradiated area, and levels of the pro-apoptotic protein BAX were increased. Intravitreal injection of a PI3K/Akt inhibitor immediately after PDT increased BAX levels and photoreceptor cell apoptosis. CONCLUSION: Cytotoxic stress caused by PDT, at levels that do not cause overt tissue damage, induces VEGF and activates Akt to rescue the neural tissue, suppressing BAX. Thus, the immediate and transient induction of VEGF after PDT is neuroprotective.